Cassava brown streak virus has a rapidly evolving genome: implications for virus speciation, variability, diagnosis and host resistance - Alicai, Titus; Ndunguru, Joseph; Sseruwagi, Peter; Tairo, Fred; Okao-Okuja, Geoffrey; Nanvubya, Resty; Kiiza, Lilliane; Kubatko, Laura; Kehoe, Monica A.; Boykin, Laura M. (Scientific reports, 2016)
Cassava is a major staple food for about 800 million people in the tropics and sub-tropical regions of the world. Production of cassava is significantly hampered by cassava brown streak disease (CBSD), caused by Cassava brown streak virus (CBSV) and Ugandan cassava brown streak virus (UCBSV). The disease is suppressing cassava yields in eastern Africa at an alarming rate. Previous studies have documented that CBSV is more devastating than UCBSV because it more readily infects both susceptible and tolerant cassava cultivars, resulting in greater yield losses. Using whole genome sequences from NGS data, we produced the first coalescent-based species tree estimate for CBSV and UCBSV. This species framework led to the finding that CBSV has a faster rate of evolution when compared with UCBSV. Furthermore, we have discovered that in CBSV, nonsynonymous substitutions are more predominant than synonymous substitution and occur across the entire genome. All comparative analyses between CBSV and UCBSV presented here suggest that CBSV may be outsmarting the cassava immune system, thus making it more devastating and harder to control.
Keywords: Cassava brown streak virus; Genome; Virus speciation; Resistance